2014
DOI: 10.3109/09638288.2014.964374
|View full text |Cite
|
Sign up to set email alerts
|

Oral health, medical diagnoses, and functioning profiles in children with disabilities receiving paediatric specialist dental care – a study using the ICF-CY

Abstract: It was possible to identify profiles of functioning in children with disabilities receiving specialist dental care. Despite complex disabilities, the children had good oral health. Neither medical diagnosis nor functioning was found to have a clear relationship with oral health. To understand the environmental context leading to high-quality oral health, further studies of dental management in relation to medical and oral diagnoses and child functioning are needed. [Box: see text].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 31 publications
0
16
0
Order By: Relevance
“…In a study of Swedish children with disabilities, Norderyd et al . did not find a relationship between child functioning and dental caries. Although not equivalent to interpersonal interactions, Dourade et al .…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…In a study of Swedish children with disabilities, Norderyd et al . did not find a relationship between child functioning and dental caries. Although not equivalent to interpersonal interactions, Dourade et al .…”
Section: Discussionmentioning
confidence: 87%
“…Specific medical diagnoses were not found to be significantly related to either child functioning in the dental setting or oral health in an ICF-CY study involving a group of Swedish children with disabilities 16 . Another study by Norderyd et al showed that a child's functioning has an impact on the choice of dental treatment modality, where children with limitations in interpersonal interactions and relationships were more likely to have had the experience of DGA 11 .…”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations
“…However, other studies have shown that the prevalence of dental caries in children with (DS) is relatively low compared to other mentally retarded or normal children. 3,4 It has beenreported that the lower prevalence of dental caries may be caused by different environmental factors, congenital oligodontia, delayed eruption, or a different salivary composition from people without (DS). However, in several studies, acidity in the oral cavity, the salivary buffer capacity, and the number of bacteria were not significantly different from those without (DS).…”
Section: Introductionmentioning
confidence: 99%